Correlative STEM-HAADF and STEM-EDX tomography for the 3D morphological and chemical analysis of semiconductor devices. (22nd January 2021) - Jacob, Martin; Sorel, Julien; Pinhiero, Rafael Bortolin; Mazen, Frederic; Grenier, Adeline; Epicier, Thierry; Saghi, Zineb
Abstract: 3D analysis of an arsenic-doped silicon fin sample is performed in a transmission electron microscope (TEM). High angle annular dark-field scanning TEM (STEM-HAADF) and energy-dispersive x-ray spectroscopy (STEM-EDX) modes are used simultaneously to extract 3D complementary multi-resolution information about the sample. The small pixel size and angular step chosen for the STEM-HAADF acquisition yield reliable information about the sidewall roughness and the arsenic clusters' average volume. The chemical sensitivity of STEM-EDX tomography gives insights into the 3D conformality of the arsenic implantation and its depth distribution. Non-negative matrix factorization method is employed to identify the chemical phases present in the sample automatically. A total variation minimization algorithm, implemented in 3D, produces high-quality volumes from heavily undersampled datasets. The extension of this correlative approach to electron energy-loss spectroscopy STEM tomography and atom probe tomography is also discussed.